Pyriform aperture enlargement in all aspects. Issue 6 (27th February 2017) - Esen, E; Bayar Muluk, N; Altintoprak, N; Ipci, K; Cingi, C
Abstract: Background: The pyriform aperture comprises the central area of facial bone structure. It is formed by the free corners of the nasal bone and the frontal processes of the maxillae, which articulate with each other at the nasomaxillary suture lines. Congenital nasal pyriform aperture stenosis might be linked to various craniofacial problems. This review presents all aspects of pyriform aperture stenosis and enlargement. Methods: A literature search was conducted. Pyriform aperture definition, nasal development, congenital nasal pyriform aperture stenosis and pyriform aperture enlargement were reviewed. Results: One of the most common abnormalities is holoprosencephaly, which is a midline developmental deficiency that may also be present in combination with facial clefting. The aetiology of nasal pyriform aperture stenosis remains unclear. When diagnosed, the choice of treatment is between non-surgical and operative methods, depending on the seriousness of the problem. Provided the sufferer can maintain a secure air passage with the help of specialised medical procedures and respiratory tract adjuvants, operative therapy may be delayed. Conclusion: The operative outcomes are extremely good, and the prognosis relies mainly on coexisting neural and endocrine problems. This paper evaluates the nasal pyriform aperture in detail.